Management of Baitulmaal Muamalat (BMM) East Java Representative in Management of Productive Waqf in the Real Sector - Uswatun Chasanah (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2024)
This study aims to analyze the management of productive waqf in the real sector by highlighting the partnership between Baitulmaal Muamalat (BMM) and Ayam Bakar Pak D outlet Kartini, Sidoarjo. This study uses a qualitative approach through a field study method to explore the implementation of productive waqf management applied by BMM. Primary data was obtained through in-depth interviews with BMM managers, while secondary data was taken from internal documents and related publications. Data analysis was carried out using the Bogdan and Taylor interactive model. The results of the study indicate that the management of productive waqf in the real sector at the outlet is quite effective, with the implementation of management functions including planning, organizing, actuating, and controlling. The benefits generated from this partnership have contributed to improving the socio-economic welfare of the community. However, there are obstacles in the form of a lack of diversification of management sectors and operational challenges that require a thorough evaluation. The implications of this study highlight the importance of developing innovations in Sharia business models and optimizing partnerships in supporting the sustainability of productive waqf.